Caries Experience and Salivary Heat Shock Proteins in Children: A Study in Humid Iraqi Marshlands - Haneen Najim Abed; Ban Sahib Diab ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2026)
This comparative cross-sectional research aims to evaluate the salivary heat shock protein association with dental caries experience in primary school students living in humid Iraqi Marshlands area compared to their peers in Al-Nasiriyah city. 400 students (6–9 years old) were volunteered in the study. A significant difference in salivary factors and prevalence of dental caries among the two groups were noticed. Also, Marshland’s students showed a significantly lower dental caries in comparison to those from Al-Nasiriyah. It reflects the effect of dietary and environmental features on oral health. As well, Marshlands group shows a higher level of salivary pH demonstrating a more alkaline salivary environment which may contribute to caries risk reduction. The outcomes highlight the importance of understanding the interaction between dietary, environmental, and oral health factors. Further research exploring the relationships between salivary indicators and dental caries experience as well as potential interventions to enhance oral health in at-risk populations are recommended.DOI: https://doi.org/10.54633/2333-024-057-001